2008
DOI: 10.3201/eid1409.080455
|View full text |Cite
|
Sign up to set email alerts
|

Juquitiba-like Hantavirus from 2 Nonrelated Rodent Species, Uruguay

Abstract: Serologic and genetic analyses indicate that a Juquitiba-like hantavirus circulates in Maldonado, Uruguay. This virus is carried by 2 rodent species, Oligoryzomys nigripes and Oxymycterus nasutus. The same hantavirus in 2 nonrelated species can be explained by a spillover infection or a host-switching event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 12 publications
5
31
0
Order By: Relevance
“…We found highly similar hantaviruses (JUQ-like virus) occurring in three distantly related rodent species (O. nigripes, A. montensis and Oxy. judex) in the same location, in agreement with the identification of a JUQ-like virus in two different species in Uruguay: O. nigripes and Oxymycterus nasutus (Delfraro et al, 2008). This could be due to an incidental infection of A. montensis and Oxy.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…We found highly similar hantaviruses (JUQ-like virus) occurring in three distantly related rodent species (O. nigripes, A. montensis and Oxy. judex) in the same location, in agreement with the identification of a JUQ-like virus in two different species in Uruguay: O. nigripes and Oxymycterus nasutus (Delfraro et al, 2008). This could be due to an incidental infection of A. montensis and Oxy.…”
supporting
confidence: 87%
“…2b). Taken together, our analyses of S and M segments demonstrated that the sequences of ARAUV isolates were very similar to JUQV isolates reported by others (Delfraro et al, 2008;Suzuki et al, 2004), and, due to historical precedence, we propose that ARAUV should be named JUQ-like virus.This study provides additional evidence that the scenario of hantavirus transmission in South America could be more complex than previously thought. We found highly similar hantaviruses (JUQ-like virus) occurring in three distantly related rodent species (O. nigripes, A. montensis and Oxy.…”
supporting
confidence: 85%
See 3 more Smart Citations